The circuit automotive campus park - Magno, Angela A. (College of Architecture, University of the Philippines Diliman, 2018)
This is an agenda based design. The Circuit is located in City of Santa Rosa, Laguna where most automotive manufacturers are located. It is dubbed as the Motor City of the South. The project is determined through addressing relevant issues of the city and utilizing different opportunities that the city offers. Focusing on what automotive industry needs. The Circuit have three agenda: Tech-Voch Education, Community and Tourism. It aims to promote and support the industry by providing a designed facility that will work through Public-Private Partnership. This Circuit is developed to integrate different functions into one facility. This project came up with a building where learning and recreation exists together. It is an automotive facility that would educate the tourists and the local working population in one development. In this project there are exhibition, educational and recreational spaces. The Circuit can accommodate 400 museum visitors, 200 students and will be around 50 employees in its functional spaces.